A Discrete Imperialist Competitive Algorithm for WSN Deployment - Jadidy Aval, Kamal; Damrudi, Masumeh (International Journal of Engineering and Technology, 2018)
The WSN deployment problem is addressed in this paper. The problem applies to the monitored areas with different detection needs at different points. In this problem, every point of the terrain is assigned with a predefined minimum probability of event detection. The objective is providing the best position for the network nodes and at the same time assuring event detection, detection message delivery, and reducing deployment cost. We have formulated the problem as an optimization problem with three objectives, which is NP-complete. Because of the huge solution space for the problem and the exponential computational complexity, none of the exact methods known yet can solve the problem unless for a pretty small scaled case. To battle the complexity of the solution, a new scalable solution is proposed based on imperialist competitive algorithm namely imperialist competitive deployment algorithm (ICDA). We compare the proposal to the related deployment strategies, and the results show that ICDA outperforms them.Â Â